Physical and Mechanical Properties Concrete Block Made from Rice Husk - Lasino Lasino; Bambang Sugiharto (Masyarakat Peneliti Kayu Indonesia, 2013)
The objectives of this research were to analyze the physical and mechanical properties of con block and paving block composites made from rice husk. Cement and aggregate ratio for con block and paving block were set at 1:6, 1:8, 1:10, and 1:4, 1:6, respectively. The content of rice husk ash in aggregate was varied from 0 to 60%. The physical and mechanical properties of concrete composite were evaluated. The results indicated that with or without rice husk ash addition, the higher the portion of aggregate added resulted in the lower the density and compression strength of con block and paving block. The higher the portion of rice husk ash added also resulted in the lower the density and compression strength of con block and paving block. Addition of rice husk up to 40% on the cement and aggregate mixtures with ratio of 1:6 resulted in con block composite with B2 grade. Addition of rice husk up to 60% on the cement and aggregate mixture with ratio of 1:4 resulted in paving block composite with 2nd state.Key words: building material, compression strength, con block, paving block, rice husk